On the Connection Between the Order of Riemann-Liouville Fractional Calculus and Hausdorff Dimension of a Fractal Function (Analysis in Theory and Applications, 2016)
This paper investigates the fractal dimension of the fractional integrals of a fractal function. It has been proved that there exists some linear connection between the order of Riemann-Liouville fractional integrals and the Hausdorff dimension of a fractal function.
Keywords: Fractional calculus; Hausdorff dimension; Riemann-Liouville fractional integral.